전신기혈요법 치료를 통해 Unified Parkinson’s Disease Rating Scale, Heart Rate Variability 및 삶의 질이 변화된 파킨슨 환자 4례에 대한 증례보고 - 목서희(Seo-Hee Mok); 이지원(Ji-Won Lee); 이태종(Tae-Jong Lee); 서정복(Jung-Bok Seo); 김경아(Kyoung-Ah Kim); 김조영(Joe-Young Kim); 박병준(Byung-Jun Park); 김동희(Dong-Hee Kim) (동의생리병리학회지, 2021)
Parkinson's disease is one of the typical neurodegenerative disease and it is caused by the destruction of substantia nigra in brain leading to lack of dopamine secretion, and it presents 4 major motor symptoms such as tremor, bradykinesia, stiffness, postural instability. Furthermore, it causes many non-motor symptoms such as anosmia, REM sleep conduct disorder, orthostatic hypotension, dementia and autonomic ataxia such as lack of adjusting blood pressure, hyperhydrosis, constipation. Dopaminergic therapy is the most commonly used strategy, but long term treatment of levodopa induce various adverse effects. Thus, many people are focusing on new therapies other than established therapies, and there are many tries and approaches with paradigm shift. Our medical team was able to get 4 cases of PD patients who are hospitalized in our hospital, treated by Whole Body Gi-Hyeol Therapy consisting of acupuncture therapy, herbal therapy, and mental therapy, and their conditions improved in perspective of Unified Parkinson's Disease Rating Scale(UPDRS), Heart Rate Variability(HRV), and Quality of life. Among all 4 cases, UPDRS score and quality of life score is gotton better, and among 2 cases SDNN, RMS-SD, TP, LF, HF scores are finely increased. And PDQ-39 score which shows quality of life is also improved. However, in spite of these improvements and positive results, there were no meaningful improvement in a hurt from a fall which is important to the aged, muscular atrophy which causes bone fracture and SMI(Skeletal Muscle Mass Index) which is indicator of osteoporosis. Thus, supplementary treatment about Whole Body Gi-Hyeol Therapy such as more active nutrition intervention, safe and effective kinesitherapy is needed, and from now on continuous case reports and systematic clinical research which has control group must be carried out.